Effect of storing conditions on the color of distillate Tuzemák - Naděžda Vaňková; Luděk Hřivna; Veronika Kouřilová; Tomáš Gregor; Renáta Dufková; Jana Simonová; Miroslav Jůzl; Iva Burešová (Kvasný průmysl)
Changes in the color of a Tuzemák distillate were monitored over a period of 24 months. The experiment was designed in cooperation with the manufacturer. The manufacturer was looking for a suitable type of bottle to sale the product. Dark and clear glass bottles with Tuzemák were stored in two temperature regimes (6 °C, 20 °C). The bottles were placed i) in a dark room, ii) in a room with daylight and iii) under LED fluorescent lighting. Color changes were monitored during the storage period using a Konica Minolta CM 3500d spectrophotometer. The results confirmed that storage conditions have a significant effect on color stability. The most stable color was observed in Tuzemák’s samples stored in a dark bottle in a dark room at low temperatures (± 6 °C). The effect of light and temperature on storage in dark bottles was weaker than in clear bottles. The color of the samples stored in clear bottles at higher temperatures was paler than that of the samples stored in dark bottles at low temperatures.